ANALISIS HARGA POKOK PRODUKSI DAN KEUNTUNGAN USAHA PEMBIBITAN LADA DI DESA SUKADANA BARU KECAMATAN MARGA TIGA KABUPATEN LAMPUNG TIMUR - Yesi Agus Riani; Wan Abbas Zakaria; Teguh Endaryanto (Lampung University, 2021)
This research aims to analyze the main production cost and profit of local and recommended pepper breeding in Sukadana Baru Village, Marga Tiga Subdistrict, East Lampung Regency. Respondents are ten pepper breeding farmers divided into three groups based on the amount of production and length of business. The data were collected in March - April 2019. This research used a survey method where the qualitative and quantitative analysis are utilized as the data analysis tools. The quantitative analysis is utilized to analyze the main production cost and profit. The qualitative analysis is used to differentiate the main production cost and profit from each group. The results show that the cost production of local pepper breeding with variable costing method ranges from IDR1,103.86 - IDR1,466.68 and with the full costing method ranging from IDR1,351.71-IDR1,754.59. The basic cost of recommended pepper breeding with variable costing method ranges from IDR821.83-IDR1,011.09 and with the full costing method ranging from IDR1,011.90-IDR1,305.09. Local pepper breeding generated profit for cash costs in one year amounting to IDR1,516.08-IDR3,527,046.65 and for a total cost of IDR1,016,002.78-IDR2,764,370.65, the recommended pepper breedings generated profit from cash costs a year amounting to IDR4,823,589.37-IDR12,628,495.56 and over total cost of IDR2,297,595.11-IDR8,763,441.85. Key words: breeding, pepper, profit, the main production cost.